Enhancing reading skills through innovative pedagogical approaches: A lesson study research investigation - M. Misnar; Burhanuddin Yasin; Izarul Machdar; Iskandar Samad; Silvi Listia Dewi; M. Misnawati (Universitas Muhammadiyah Malang, 2025)
The research demonstrates that the implementation of an innovative approach using the lesson study model and interactive digital reading books effectively enhances students' reading skills. The study shows a significant improvement in students' reading skills after the implementation of the innovative pedagogical approach. This research utilizes experimental research with a pre-test post-test design approach. The samples consists of 35 students. By utilizing the lesson study approach and interactive digital reading books, students exhibited an increase in the average reading test scores from 62.00 in the pretest to 86.57 in the posttest, with an n-gain score of 0.62 falling into the medium category. The paired samples t-test analysis also indicates a significant difference in students' learning outcomes before and after the implementation of the innovative approach. Therefore, the research provides a strong foundation for the application of innovative teaching methods to enhance students' reading skills. Additionally, the use of interactive digital reading books allows for the adjustment of reading difficulty levels according to individual students' needs and abilities, enabling more differentiated learning. Thus, the use of interactive digital reading books can be considered an effective innovative method for improving students' reading skills.